Profil Level of Physical Conditions for Basketball - Priyanto Priyanto; Haris Kurnianto; Herdiyan Agung Prakoso; Arief Setyo Pranoto (Universitas Negeri Semarang, 2023)
Abstract. The purpose of this study was to determine the level of physical condition of the Academy Jaguar Basketball athletes in Semarang City in 2022. The population of this study was all athletes in the Academy Jaguar Basketball Semarang City in 2022, totaling 12 athletes. The sample used in this study used total sampling. The results showed that the average score of the athlete's physical condition level was 2.65 which was included in the less category. Judging from the level of physical condition of each athlete, it is known that there are 9 students (75%), then a number of 3 athletes (25%) in the category are moderate. This study concluded that the physical condition of the basketball athletes at the Jaguar Basketball Academy was in the poor category. Abstract in Indonesia. Penelitian ini memiliki tujuan yaitu mengetahui tingkat kondisi fisik atlet Academy Jaguar Basketball Kota Semarang Tahun 2022. Penelitian ini memilih populasi yaitu keseluruhan atlet Academy Jaguar Basketball Kota Semarang Tahun 2022 yang berjumlah 12 atlet Sampel yang digunakan dalam penelitian ini menggunakan total sampling. Hasil penelitian menunjukkan kategori kondisi fisik atlet disimpulkan kurang dengan nilai rerata 2,65. Terdapat sebanyak 9 atlet (75%) yang masuk kondisi kurang sedangkan sisanya 3 atlet kondisinya sedang (25%). Penelitian ini memperoleh kesimpulan bahwa kondisi fisik atlet para atlet bola basket di Academy Jaguar Basketball berkategori kurang.